Encapsulated Cell Dynamics in Droplet Microfluidic Devices with Sheath Flow - Beshay, Peter E. (Micromachines (Basel), 2021)
In this paper we study the dynamics of single cells encapsulated in water-in-oil emulsions in a microchannel. The flow field of a microfluidic channel is coupled to the internal flow field of a droplet through viscous traction at the interface, resulting in a rotational flow field inside the droplet. An encapsulated single cell being subjected to this flow field responds by undergoing multiple orbits, spins, and deformations that depend on its physical properties. Monitoring the cell dynamics, using a high-speed camera, can lead to the development of new label-free methods for the detection of rare cells, based on their biomechanical properties. A sheath flow microchannel was proposed to strengthen the rotational flow field inside droplets flowing in Poiseuille flow conditions. A numerical model was developed to investigate the effect of various parameters on the rotational flow field inside a droplet. The multi-phase flow model required the tracking of the fluid–fluid interface, which deforms over time due to the applied shear stresses. Experiments confirmed the significant effect of the sheath flow rate on the cell dynamics, where the speed of cell orbiting was doubled. Doubling the cell speed can double the amount of extracted biomechanical information from the encapsulated cell, while it remains within the field of view of the camera used.